PUBLIC PERCEPTION OF COVID-19 VACCINE EFFECTIVENESS IN MALAYSIA: A SCOPING REVIEW - Rusaznan, Maizatul Shazwani Mohd; Md Yusoff, Yusnaini; Hashim, Nur Asmadayana; Arham, Ahmad Firdhaus; Rusly, Noor Sharizad; Zainal, Nur Hafiza; Mokhtar, Mohd Istajib; Chin , Kim Ling (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This scoping review explores the public perception of COVID-19 vaccine effectiveness in Malaysia, a topic crucial to improving vaccine uptake in a diverse sociocultural setting. The study aims to identify key influencing factors, thematic patterns, and research gaps related to vaccine acceptance. Guided by PRISMA-ScR methodology, a systematic literature search was conducted using Scopus, PubMed, MyJurnal, and Google Scholar for studies published between January 2020 and February 2024. Fifteen relevant articles were selected based on inclusion criteria focusing on Malaysian populations. Thematic analysis revealed five dominant themes: sociodemographic determinants, misinformation, trust in institutions, health literacy, and cultural-religious influences. Findings suggest that vaccine confidence is higher among younger, urban, and educated individuals, while hesitancy persists among older adults, rural populations, and those with low health literacy or religious concerns. Social media plays a dual role as both an information source and a misinformation channel. The study underscores the need for transparent, culturally sensitive communication strategies and emphasizes the involvement of trusted figures such as healthcare providers and religious leaders. This review contributes to public health discourse by highlighting actionable insights for policy-making, communication planning, and future empirical research on vaccine confidence in Malaysia.